A multi-risk SIR model with optimally targeted lockdown - Daron Acemoglu; Victor Chernozhukov; Iván Werning; Michael D. Whinston (Centre for Microdata Methods and Practice (cemmap), 2020)
We develop a multi-risk SIR model (MR-SIR) where infection, hospitalization and fatality rates vary between groups-in particular between the "young", "the middleaged" and the "old". Our MR-SIR model enables a tractable quantitative analysis of optimal policy similar to those already developed in the context of the homogeneousagent SIR models. For baseline parameter values for the COVID-19 pandemic applied to the US, we find that optimal policies differentially targeting risk/age groups significantly outperform optimal uniform policies and most of the gains can be realized by having stricter lockdown policies on the oldest group. For example, for the same economic cost (24.3% decline in GDP), optimal semi-targeted or fully-targeted policies reduce mortality from 1.83% to 0.71% (thus, saving 2.7 million lives) relative to optimal uniform policies. Intuitively, a strict and long lockdown for the most vulnerable group both reduces infections and enables less strict lockdowns for the lower-risk groups. We also study the impacts of social distancing, the matching technology, the expected arrival time of a vaccine, and testing with or without tracing on optimal policies. Overall, targeted policies that are combined with measures that reduce interactions between groups and increase testing and isolation of the infected can minimize both economic losses and deaths in our model.
Keywords: 330; Coronavirus; Epidemie; Shutdown; Impfung; Sterblichkeit; Wirtschaftlicher Schaden; Altersgruppe; Modellierung